STIMULATION OF CRITICAL AND CREATIVE THINKING PROCESS THROUGH PSYCHOLOGICAL WORKSHOPS AMONG POSTGRADUATE STUDENTS - Marijana Markovikj; Eleonora Serafimovska (Goce Delcev University in Shtip, Republic of Macedonia, 2016)
Stimulation of critical and creative thinking process is the most essential aspect of shaping democratic citizens’ identity and ideology, which have influence in establishing citizenship society. But, in the process of satisfying our ego, our tendency to see world only through our wishes and needs, we can often deny ourselves intellectual growth and opportunity. Critical thinking includes a complex combination of skills. Among the main characteristics are the following: rationality, self-awareness, honesty, open-mindless, moral judgment etc. Psychological laboratory at the Institute for sociological, political and juridical research, Skopje, established block of 10 workshops with 6 groups of post-graduated students. Each workshop has different topic: building self-capacity, stimulation of communication skills, emotional management, conflicts, motivation stress management, stimulation of moral judgment competence etc. The workshop process by itself has character of research in action. Changes among students happened during each workshop. Some of effect which have been shared in the groups are following: students become more aware about themselves and others, they can control their emotions and can manage arising conflicts. Other thing is that they find this process of learning as very effective in their professional life and academic too. They shared that this process stimulated their process of changes in personality and identity.
Keywords: psychological workshops, democratic citizen’s identity, creative and critical thinking, postgraduate students